Prognostic markers of symptomatic congenital cytomegalovirus infection - Romanelli,Roberta Maia de Castro (2008)
The objective of this research was to identify maternal and fetal characteristics as prognostic markers of congenital cytomegalovirus (CMV) infection. This is a descriptive study of 13 cases of congenital CMV infection referred to Institute de Puericulture et Perinatologie de Paris (IPP) from January 2005 to October 2006. Amniotic fluid puncture was performed to research CMV polimerase chain reaction (PCR). Cordocentesis and cord blood samples at delivery were also analyzed to determinate fetal platelets count, GGT, ASAT, ALAT, CMV-DNA and IgM antibody. Variables of symptomatic and asymptomatic infants were then compared. Data were analyzed by SPSS - 15.0. Mean gestational age of amniocentesis was 24.6 weeks and there was no difference of mean viral load in amniotic fluid considering infant features. Mean gestational age of cordocentesis was 26.1 weeks. There were no statistical differences of fetal viral load, IgM, platelets, GGT, ASAT and ALAT analyzed at cordocentesis samples, but at delivery, mean values of IgM and ASAT of fetal blood were increased in symptomatic ones (p= 0.03 for both parameters). When considering groups with normal and abnormal parameters, ASAT of cordon samples was also increased in symptomatic infants (p= 0.02). Sensibility, specificity, positive and negative predictive value of fetal ultrasound anomalies to detect symptomatic infants were, respectively, 80%, 62.5%, 57.1% and 83.3%. Thus, identification of markers of CMV symptomatic infants should be aimed. Prenatal diagnosis, identification and follow up of congenital CMV infected infants are important to consider treatment for symptomatic infants, trying to avoid or reducing some possible sequels.